MOTIF KECENDERUNGAN PERILAKU FRAUD ASN: PERSPEKTIF FRAUD DIAMOND THEORY - Budirahayu, Paramita; Asedica Pesudo, David Adechandra (Faculty of Economics and Business University of Mataram, 2023)
This study uses the Fraud Diamond Theory approach to explore the motives of the State Civil Apparatus in the Regional Apparatus Organization City X. This research is a qualitative descriptive study using primary data collection techniques. Data collection began with semi-structured interviews with representatives of the State Civil Apparatus in each section of Regional Apparatus Organization City X and deepened through observation. The results of this study indicate that fraud is still found in the form of asset misuse by the State Civil Apparatus. The tendency for fraudulent behavior to occur is based on an intention within the Regional Apparatus Organization to commit fraud driven by motives in the form of pressure, rationalization, opportunity, and ability, as explained in the Fraud Diamond Theory. The results of this study can be used as evaluation material for City X Regional Apparatus Organizations to mitigate the possibility of fraud.